2019
DOI: 10.12669/pjms.35.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of miltefosine in cutaneous leishmaniasis: An open label, non-comparative study from Balochistan

Abstract: Background & Objective: Cutaneous Leishmaniasis (CL) is endemic in Baluchistan and treated traditionally with Meglumine antimoniate. Miltefosine appears appealing therapy in cutaneous Leishmaniasis. Our objective was to evaluate safety and efficacy of Miltifossine in treatment of cutaneous Leishmaniasis. Methods: This experimental study was conducted from 10 September 2017 to 10 May 2018 at Combined Military Hospital Quetta. Total of 42 patients were recruited by purposive sampling technique. Lesiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Venous blood sampling was conducted four times on different days to quantify the number of inflammatory cells in the same participant ( n = 467), revealing that the mean intraindividual CV was below 10% in the complete blood count [ 61 ]. Tahir et al [ 62 ] also reported that no significant difference was noted on different days. The CVs of PLR on different days in the same patient were small, which did not lead to bias in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Venous blood sampling was conducted four times on different days to quantify the number of inflammatory cells in the same participant ( n = 467), revealing that the mean intraindividual CV was below 10% in the complete blood count [ 61 ]. Tahir et al [ 62 ] also reported that no significant difference was noted on different days. The CVs of PLR on different days in the same patient were small, which did not lead to bias in the results.…”
Section: Discussionmentioning
confidence: 99%
“…The orally administered drug miltefosine (hexadecylphosphocholine) was first used as an anticancer agent before it was suggested as a treatment for leishmaniasis [ 25 , 50 ]. Studies have proven antileishmanial activities associated with its ability to derange sterol and phospholipid biosynthesis, and cell signal transduction of parasites [ 51 ].…”
Section: Antileishmanial Monotherapymentioning
confidence: 99%
“…Studies have proven antileishmanial activities associated with its ability to derange sterol and phospholipid biosynthesis, and cell signal transduction of parasites [ 51 ]. In some instances, where antimony resistance had become a challenge, miltefosine was used as the second-line drug [ 25 ] and was effective on diffused CL producing 80–90% parasitological improvement within 2 months [ 52 ]. Nonetheless, this regime resulted in high probability of relapsing with the development of new infection in the majority of cases [ 52 ].…”
Section: Antileishmanial Monotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Miltefosine is registered in Pakistan for use in leishmaniasis (produced and sold under the name Fosine). However, until now, only limited case studies have been conducted to evaluate the efficacy of miltefosine in CL caused by L. tropica which is generally considered to be less drug sensitive [24][25][26]. It is not (yet) included in the Pakistan national guidelines, although it is recommended by the WHO in the manual for case management of CL in the EMRO region (2014) as a second line treatment [27,28].…”
Section: Introductionmentioning
confidence: 99%